2009
DOI: 10.1590/s0124-00642009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Estado Nutricional de Escolares do Semi-Árido do Nordeste Brasileiro

Abstract: Adolescents in the most favored regions (especially students in private schools in the region) had a prevalence of being overweight and suffering from obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
4
0
7
Order By: Relevance
“…[29][30] The same trend was observed in Pernambuco, where excess weight was significantly higher among children and adolescents from families with a higher income and a better socioeconomic level. 25,31 In the South of the country, in Santa Catarina, the results found in a study of students enrolled in the public and private networks were similar to our research, as a significant association was identified between excess weight and income. 32 Although physical exercise was not associated with overweight in this study, research shows that a higher family income can provide greater access to consumption goods that stimulate sedentariness, like the computer.…”
Section: Discussionsupporting
confidence: 87%
“…[29][30] The same trend was observed in Pernambuco, where excess weight was significantly higher among children and adolescents from families with a higher income and a better socioeconomic level. 25,31 In the South of the country, in Santa Catarina, the results found in a study of students enrolled in the public and private networks were similar to our research, as a significant association was identified between excess weight and income. 32 Although physical exercise was not associated with overweight in this study, research shows that a higher family income can provide greater access to consumption goods that stimulate sedentariness, like the computer.…”
Section: Discussionsupporting
confidence: 87%
“…Esses achados corroboram os de Campos et al 28 , os quais, em pesquisa com 1.158 escolares da cidade de Fortaleza, constataram que o excesso ponderal se concentrava entre os escolares da rede particular de ensino. Silva et al 31 também identificaram tendência similar nos estudantes de melhor nível econômico do semiárido brasileiro.…”
Section: Discussionunclassified
“…For calculation of the sample size (n), a 10% prevalence of overweight and obesity was adopted, as observed in a study with Brazilian children of low socioeconomic status, 9 obtaining n = 548 children, considering a margin of error (e) of 5% and a confidence level of 95%.…”
Section: Methodsmentioning
confidence: 99%